Propuesta de mejora a la gestión por procesos de proyectos de vinculación de la ESPAM-MFL aplicando técnica de medición de tiempos - Almeida Zambrano, Ramón Gustavo (2018)
The present study was carried out with the objective of proposing improvements to the management by processes of projects of connection with the community of the Polytechnical Superior School of Manabí Manuel Félix López, through the application of the technique of measurement of times. In order to fulfill this purpose, scientific research tools were applied, such as the interview, which allowed the methodological development of the research and graphical representation of the processes, clearly and simply showing their trajectory. The methods that were applied and complied with the phases of the investigation were the inductive which served to determine the causes of the existing shortcomings, the deductive method allowed to indicate the main ideas of the process under study and the analytical method helped to carry out an analysis of each of the activities that take place in the process mentioned. Once the research methods and techniques were applied, time was measured in the process under study, resulting in an effective process, however, from the execution activities of the projects, the schedule begins to expand for budgetary reasons, since in the designation there are delays due to lack of economic availability. Hence, the application of improvement actions that help to counteract these problems and improve the process increase, increasing productivity, efficiency and effectiveness, while optimizing time and resources for the institution and each dependency that exists.